Clinical evaluation of desensitizing treatments for cervical dentin hypersensitivity - Ana Cecilia Corrêa Aranha; Luiz André Freire Pimenta; Giselle Maria Marchi (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The aim of this study was to compare different treatments for dentin hypersensitivity in a 6-month follow-up. One hundred and one teeth exhibiting non carious cervical lesions were selected. The assessment method used to quantify sensitivity was the cold air syringe, recorded by the visual analogue scale (VAS), prior to treatment (baseline), immediately after topical treatment, after 1 week, 1, 3 and 6 months. Teeth were randomly assigned to five groups (n = 20): G1: Gluma Desensitizer (GD); G2: Seal&Protect (SP); G3: Oxa-gel (OG); G4: Fluoride (F); G5: Low intensity laser-LILT (660 nm/3.8 J/cm²/15 mW). Analysis was based on the non-parametric Kruskal-Wallis test that demonstrated statistical differences immediately after the treatment (p = 0.0165). To observe the individual effects of each treatment, data was submitted to Friedman test. It was observed that GD and SP showed immediate effect after application. Reduction in the pain level throughout the six-month follow-up was also observed. In contrast, LILT presented a gradual reduction of hypersensitivity. OG and F showed effects as of the first and third month respectively. It can be concluded that, after the 6-month clinical evaluation, all therapies showed lower VAS sensitivity values compared with baseline, independently of their different modes of action.